The finish line location of the cemented crown is an influencing factor for tensile bond strength, marginal adaption and nanoleakage? - Angelo, Enrico; Lins, Rodrigo Esteves Barros; Martins, Luis Roberto Marcondes (Brazilian Dental Science, 2020)
Objective: The aim of this study was to evaluate the influence of different crowns finishing line location on the crown tensile bond strength, marginal adaption and nanoleakage. Material and Methods: Sixty healthy third molars were collected. For tensile bond strength, a self-adhesive resin cement was used. For marginal adaption, epoxy resin models were prepared. Prior to tensile bond strength test, images for the epoxy resin models were measured under scanning electron microscopy (SEM). Nanoleakage was measured using same protocol. Failure mode was evaluated through SEM and classified: adhesive failure, cohesive in cement, cohesive in dentin, cohesive in resin composite, cohesive in enamel, and mixed. Statistical analysis was performed using Shapiro-Wilk and Kolmogorov Smirnov normality tests, two-way ANOVA, Bonferroni (posthoc) parametric test, with significance level of 5% (P < .05), Spearman correlation test. Results: tensile bond strength was not statistically different between the cemented groups with composite resin and ceramic. Cementation of ceramic was not statistically different between the groups (enamel, 3.28 Pa; dentin, 3.14 Pa; resin, 2.85 Pa). Marginal adaption was statistically different between resin and ceramic; finish line location varied between enamel and resin (175.91 ?m vs. 433.58 ?m). Nanoleakage rate was statistically different among all groups, except for resin: with resin (9.49%) and ceramic (9.35%). There was a predominance of adhesive failure in all groups. Conclusion: finish line location can be performed safely in enamel and dentin. Composite resinas substrate present an alternative, but still need to be more studied. Regarding the crown’s material, it is possible to perform a satisfatory restoration in both: resin and ceramic. With ceramics presenting better results. KEYWORDS Resin composite; Ceramics; Tensile bond strengh; Marginal adaption; Nanoleakage.